Walhi's Strategy to Fight for Justice in Environmental Permit Cancellation: Case Study of Construction of PLTU Tanjung Jati A Cirebon - Fasmalia, Putri; Angela, Deni (Journal La Sociale, 2024)
The issue of environmental permits for PLTU Tanjung Jati A is a serious problem because the publication does not include an analysis of the release of CO2 emissions which have an impact on environmental damage and climate change. This research aims to describe Walhi West Java's strategy in its efforts to cancel the environmental permit for PLTU Tanjung Jati A through its international and national networks. In line with this aim, this research uses a case study approach with data collection carried out through in-depth interviews and analysis of related documents. The theory used by the Transnational Advocacy Network (TAN) theory as an analytical tool was put forward by Margaret E. Keck and Kathryn Sikkink. The results of this research, Walhi West Java has implemented four TAN strategies, namely Information Politics by disseminating information and findings, Symbolic Politics by carrying out campaign actions with symbols, Leverage Politics by collaborating with stronger actors, and Accountability Politics by supervising actors who advocated to walk with the commitments that have been set. Based on these four strategies, Walhi West Java is very optimal in carrying out Information Politics and Leverage Politics strategies. The weakness is that the Political Accountability strategy has not been fully successful because the Tanjung Jati A PLTU project is still in the policy documents and RUPTL. Walhi West Java's TAN implementation strategy succeeded in bringing victory over the Head of DPMTSP regarding the cancellation of environmental permits.